Does Indonesia Have a "Low-Pay" Civil Service? - Filmer, Deon; Lindauer, David L. (World Bank, Washington, DC, 2014)
Government officials and polcy analysts maintain that Indonesia's civil servants are poorly paid and have been for decades. This conclusion is supported by anecdotal evidence and casual empiricism. The authors systematically analyze the realtionship between government and private compensation levels using data from two large household surveys carried out by Indonesia's Central Bureau of Statistics: the 1998 Sakernas and 1999 Susenas. The results suggest that government workers with a high school education or less, representing three-quarters of the civil service, earn a pay premium over their private sector counterparts. Civil servants with more than a high school education earn less than they would in the private sector but, on average, the premium is far smaller than commonly is alleged and is in keeping with public/private differentials in other countries. These results prove robust to varying econometric specifications and cast doubt on low pay as an explanation for government corruption.